Hedonic price formation - Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2023)
This short article provides a quick summary of the hedonic pricing theory. Some new developments are also discussed.
Keywords: C10; D10; R20; 330; hedonic price; portfolio of attributes; valuation; unobservable; non-tradeable